Pemberian Pakan Bagi Hewan Kesayangan Yang Terdampak Musibah Badai Seroja Di Nusa Tenggara Timur - Tri Utami; Tarsisius Considus Tophianong; Larry Richard Wellem Toha; Maxs Urias Ebenhaizar Sanam; Meity Merviana Laut (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2022)
Flash floods and landslides caused by tropical cyclone Seroja in East Nusa Tenggara (NTT) have caused casualties and damage to residential buildings and other public facilities. The disaster also had an impact on the animals. Many animals were swept away by the flood, and some of the animals that survived were suffered from stress and difficulty in getting food due to being abandoned by the owner to the evacuation shelter. The purpose of this activity is to rehabilitate pets that have been affected by the tropical cyclone Seroja. This service is incidental activity which is carried out for 4 (four) months, from April to July 2021. The implementing team, which is part of the academic community of the Faculty of Veterinary Medicine, University of Nusa Cendana, collaborates with the NTT Branch of the Veterinary Association and several foundations such as the Jakarta Animal Aid Network. (JAAN), Stray Cat Defender, Stay Purr Club, Tais Indonesia, PT. Royal Canin Indonesia, animal health center (puskeswan) in Kupang City, Kupang Regency, Malacca Regency, East Flores Regency, Lembata Regency and Grace Vetcare Animal Clinic. The implementation team has distributed animal feed assistance as many as 105 bags of animal feed and has provided food (street feeding) directly to pets as many as 230 dogs and 257 cats. Street feeding is a form of post-disaster animal recovery. Keywords: recovery, street feeding, tropical cyclone Seroja